CDMA-based Acoustic Local Positioning System for Portable Devices with Multipath Cancellation - Fernando J. Alvarez; Teodoro Aguilera; R. López-Valcarce (Digital Signal Processing, 2017)
This paper presents an acoustic local positioning system (ALPS) suitable for indoor positioning of portable devices such as smartphones or tablets, based on the transmission of high frequency CDMA-coded signals from a fixed network of beacons. The main novelty of the proposed ALPS is its capability to mitigate the effects of multipath propagation by performing an accurate estimation of the Line-of-Sight Time-of-Flights (LOS-TOF) through the Matching Pursuit algorithm. Signal detection, multipath cancellation and positioning estimation all take place within the portable device, which provides a graphical representation of the updated position in less than a second. The performance of the Matching Pursuit algorithm is analyzed in a real scenario and the results show that the proposed method is capable to retrieve the multipath-free System Availability under strong multipath conditions with SNR levels as low as 0 dB.
Keywords: compass; wsn